(untitled) (Research, Society and Development, 2022)
Objective: To provide an up-to-date assessment of the use of CT in cases of COVID-19. Methodology: This research belongs to an integrative review of operationalized literature, guided by the following phases: recognition of the dimension and precision of the interrogation of the literature; the exclusion and inclusion criteria; development of the chosen studies; distribution of elected works; observation of the research and clarification of the results; finally, the display of the complete review. Results: Thus, the studies were predominantly published in the year 2020, being equivalent to 75% of all articles used for the study and about 25% in the year 2021. Therefore, most of the works were from the United States 25%, against 12.5% ​​for France, 12.5% ​​for the Netherlands, 12.5% ​​for Germany, 12.5% ​​for Indonesia, 12.5% ​​for the Netherlands and 12.5% ​​for Spain. Therefore, the main findings in patients with suspected COVID-19 were found at the site: first, ground-glass opacity, second: Consolidations, third: reticular pattern, thickened interlobular septum, air bronchogram, and bronchiolectasis. Thus, the patterns characterize a certain prevalence in patients who present for CT. Conclusion: Conclusion- It is concluded that the diagnosis of Covid-19 is of extreme evaluation of patients, as it has several evolution computers for clinical follow-up, of patients, establishment of success for clinical follow-up, of patients, establishment of evolution for clinical follow-up of patients, establishment of drugs of clinical choice, even for the diagnosis of cases not identified in the RT-PCR test.